NEW RECORDS OF CHRYSOPIDAE (NEUROPTERA) IN BRAZIL - Marsaro Júnior, Alberto Luiz; Freitas, Sérgio de; Adaime, Ricardo (REVISTA DE AGRICULTURA, 2013)
This work reports certain species of Chrysopidae for the first time in the Brazilian state of Roraima, and in Brazil as well. The chrysopids were collected with McPhail traps in four municipalities of the state of Roraima, Amajari, Boa Vista, Bonfim and Pacaraima. All nine species of Leucochrysa identified in this work were reported for the first time in the state of Roraima, and L. (Nodita) amazonica (Navás) and L. (N.) pavida (Hagen) were reported for the first time in Brazil. Three species of Ceraeochrysa, namely C. acmon (Penny), C. caligata (Banks) and C. cincta (Schneider), were reported for the first time in Roraima; and C. valida (Banks) was reported for the first time in Brazil. Within the genus Plesiochrysa, P. brasiliensis (Schneider) was reported for the first time in Roraima. Species description is still required for the two new species identified in this work as Plesiochrysa sp. and Leucochrysa (N.) sp.